A cyber-physical approach to resilience and robustness by design - Di Orio, Giovanni (2021)
Modern critical infrastructures (e.g. Critical Energy Infrastructures) are increasingly evolving into complex and distributed networks of Cyber-Physical Systems. Although the cyber systems provide great flexibility in the operation of critical infrastructure, it also introduces additional security threats that need to be properly addressed during the design and development phase. In this landscape, resilience and robustness by design are becoming fundamental requirements. In order to achieve that, new approaches and technological solutions have to be developed that guarantee i) the fast incident/attack detection; and ii) the adoption of proper mitigation strategies that ensure the continuity of service from the infrastructure. The "Double Virtualization" emerged recently as a potential strategy/approach to ensure the robust and resilient design and management of critical energy infrastructures based on Cyber-Physical Systems. The presented approach exploits the separation of the virtual capabilities/functionalities of a device from the physical system and/or platform used to run/execute them while allowing to dynamically (re-) configure the system in the presence of predicted and unpredicted incidents/accidents. Internet-based technologies are used for developing and deploying the envisioned approach.